Development of Sodium Diethyldithiocarbamate-loaded Halloysite Nanotube in Epoxy as A Smart Anticorrosion Coating - ZAHIDAH, KHAIRINA AZMI (2018)
In petroleum industry, various approaches have been implemented in an effort to mitigate corrosion where protective coating is one of the most effective.